Pengolahan Ikan Bandeng Tanpa Duri Di Kelurahan Lakkang, Kecamatan Tallo, Kota Makassar - Hasnidar, Hasnidar; Tamsil, Andi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Milkfish (Chanos chanos Forskall) is a consumption fish that is quite popular in Indonesia. Thornless milkfish is a semi-finished fishery product in the form of fresh raw milkfish which has been removed from the bone. The advantage is not reducing the nutritional content because the processing only removes thorns. This activity aims to transfer the technology of thornless milkfish processing to mothers and young women in the Cahaya Lakkang and Jaya Lakkang groups in Kelurahan Lakkang, Kecamatan Tallo, Kota Makassar. The activities offered are in the form of counseling, training and field practice. The method of approach adopted is a participatory approach. Training material consists of: (1) introduction of the characteristics of fresh milk fish; (2) arrangement and number of thorns found in milkfish; (3) interesting techniques for fish spines; (4) packing practice. The results of the implementation of thornless milkfish processing indicate that: 1) increased knowledge and skills of the target audience in processing milkfish without thorns; 2) Approximate 80-70% yield of milkfish without spines.